Talent identification: What makes a champion swimmer? - Ackland, T. (coachesinfo.com, 1999)
The utility of talent identification programs for predicting swimming performance is assessed using data gathered in recent research studies. Evidence is assembled to determine whether elite swimmers differ from the normal population on strategic variables that are not easily modified through training. Further, the data clearly demonstrate that these attributes may be used to discriminate between elite performers in various strokes and event distances, as well as between the best performers and the rest of the field. The research also supports the notion that an effective talent identification program may be formulated for the sport of swimming. While a junior swimmer's current level of performance may provide a useful starting point, through our understanding that talent identification is about predicting some future potential of this individual, we should therefore seek attributes that will provide an advantage over other competitors. Of special interest are those attributes that cannot be easily modified through training, as they provide a 'natural' advantage for the swimmer when all other factors are equal. Quite clearly, tall stature and long segment lengths provide a mechanical advantage for short distance swimmers in their development of propulsive force. This tall stature allows the swimmer to increase body bulk through strength and power training, without seriously affecting active drag. Whether the forearm-plus-hand is used as a paddle or foil, it appears that longer segments are a definite advantage, as too are a pair of size 16 feet. The shorter, stockier body builds, on the other hand, appear more suited to breaststroke technique as well as to the open water, long distance events.